2012
DOI: 10.1590/s0104-07072012000500009
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of simultaneous polydrug use: risk and protective factors in undergraduate students in one university, Kingston - Jamaica

Abstract: Simultaneous polydrug use in undergraduate students was studied in one university in Kingston, Jamaica. The study was a cross-sectional, and used a survey method of data collection. We examined protective and risk factors associated with simultaneous polydrug use in a sample of 295 undergraduate students from the health and medical science departments in the university. Our results suggest that continued residence with family, family support, and students' emotional well-being are protective factors. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Additionally, consistent with previous research (e.g., McCabe et al, 2007), alcohol use was a significant risk factor for past 30-day illicit substance use, which is consistent with Mitchell et al (2012), which indicated that 6.1% of participants reported past year concurrent polydrug use (including alcohol and marijuana). Other studies (e.g., Midanik, Tam, & Weisner, 2007; Pacek, Malcolm, & Martins, 2012) have indicated that individuals who engage in polysubstance use are at an increased risk to experience aversive consequences (e.g., arrests, major depressive episodes), as well as negative health consequences from these use patterns.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, consistent with previous research (e.g., McCabe et al, 2007), alcohol use was a significant risk factor for past 30-day illicit substance use, which is consistent with Mitchell et al (2012), which indicated that 6.1% of participants reported past year concurrent polydrug use (including alcohol and marijuana). Other studies (e.g., Midanik, Tam, & Weisner, 2007; Pacek, Malcolm, & Martins, 2012) have indicated that individuals who engage in polysubstance use are at an increased risk to experience aversive consequences (e.g., arrests, major depressive episodes), as well as negative health consequences from these use patterns.…”
Section: Discussionsupporting
confidence: 89%
“…Given the paucity of research in the global context, this research examines the effects of the age of initiation and other psychosocial factors of singular drug use on polysubstance use within a nationally representative sample, thereby providing valuable insight towards policy implications on a national scale. The random selection of survey respondents in the initial study and the use of a large population sample for the current study were significant strengths, as the limited research done in Jamaica investigating polysubstance use has examined small and specific samples103 104 that produced findings that were unlikely to be generalised to a larger population. The strength of the secondary analysis conducted was enhanced by the use of logistic regression for the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…University students on the other hand, typically have higher rates of alcohol consumption which may be due in part to the social environment on campus, the ease with which alcohol can be obtained and increased autonomy from parents. [17][18][19] In addition, there is also evidence which suggests that undergraduate students drink even more than their non-student peers. 5,17 The level of hazardous alcohol use within the sample is not alarmingly high when compared to that of international studies.…”
Section: Discussionmentioning
confidence: 99%